2016
DOI: 10.1016/j.polymer.2016.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure evolution of poly[tetrafluoroethylene-co-(perfluoropropylvinylether)] films under uniaxial deformation

Abstract: This paper presents an investigation of semi-crystalline poly[tetrafluoroethylene-co-(perfluoropropylvinylether)] (PFA) films uniaxially drawn at two temperatures. The extent of crystal unit cell orientation increased significantly with drawing at both draw temperatures as expected, but crystallinity was found to increase with draw ratio only at the lower draw temperature, remaining unchanged at the higher temperature. Considering the evolution of small-angle X-ray scattering patterns as a function of deformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…Although their dielectric constants are in the same range as BOPP, they can be melt extruded into thin films, have high dielectric stability at elevated temperatures, and exhibit very low dielectric loss. 10 Building on our previous work, 11,12 we focus in this paper on the role of uniaxial orientation and subsequent thermal annealing on the semi-crystalline microstructure and low electric field dynamics of ETFE, as well as high field dielectric breakdown measurements on selected drawn and annealed ETFE films. Experimental Weibull dielectric breakdown strengths are found to increase with uniaxial orientation (draw ratio = 3) to values as high as 870 MV/cm, over 10% larger than commercial BOPP films measured under similar conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Although their dielectric constants are in the same range as BOPP, they can be melt extruded into thin films, have high dielectric stability at elevated temperatures, and exhibit very low dielectric loss. 10 Building on our previous work, 11,12 we focus in this paper on the role of uniaxial orientation and subsequent thermal annealing on the semi-crystalline microstructure and low electric field dynamics of ETFE, as well as high field dielectric breakdown measurements on selected drawn and annealed ETFE films. Experimental Weibull dielectric breakdown strengths are found to increase with uniaxial orientation (draw ratio = 3) to values as high as 870 MV/cm, over 10% larger than commercial BOPP films measured under similar conditions.…”
Section: Introductionmentioning
confidence: 99%
“…and Yin et al, respectively). In these works, both authors drew films of PFA (PEVE comonomer for Fujimori et al, PPVE comonomer for Yin et al) up to 9 times their original length at elevated temperatures (200 °C, Fujimori et al tested at 280 °C, Yin et al tested at 140 °C). , Yin et al noticed that increased crystallinity began at applied stresses near 6.5 MPa, which is near the nominal contact stress (6.25 MPa) used for this study. In our wear experiments, the local stress at the PFA interface is significantly larger than the apparent contact pressure due to roughness of the steel counterface.…”
Section: Resultsmentioning
confidence: 92%
“…Fujimori et al and Yin et al both observed strain-induced crystallinity of PFA films after uniaxial tensile stress experiments (35% and 10% increase in crystallinity for Fujimori et al . and Yin et al, respectively). In these works, both authors drew films of PFA (PEVE comonomer for Fujimori et al, PPVE comonomer for Yin et al) up to 9 times their original length at elevated temperatures (200 °C, Fujimori et al tested at 280 °C, Yin et al tested at 140 °C). , Yin et al noticed that increased crystallinity began at applied stresses near 6.5 MPa, which is near the nominal contact stress (6.25 MPa) used for this study.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations